Repellent action of cashew (Anacardium occidentale L.) nut shell liquid (CNSL) on adult papaya fruit fly Bactrocera dorsalis (Hendel) (Diptera: Tephritidae) - Keita, Sainey; Wan Fatma Zuharah, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
The fruit fly, Bactrocera dorsalis is a major pest of papaya and known to cause economic losses to the agricultural industry globally. It attacks the fruits causing premature ripening and rotting. This study aims to investigate the repellency activity of the liquid extract of the cashew nut shell using hexane and dichloromethane as extracting solvents. The repellent action of the extracts was tested by dissolving 2, 4, 6, 8, 10 μL of the extracts in 1 ml of acetone to produce concentrations of 0.07, 0.14, 0.21, 0.28, and 0.35 μL/cm2. An 85mm filter paper was cut into two equal halves which penetare with treatment and control. Both equal half discs were air-dried to evaporate the solvent completely. The treated halves to untreated halves were then remade by attaching them into full discs. The treated filter paper was placed in a petri dish, and ten fruit flies were released at the centre of the petri dish and then covered. Repellency effect was observed after 12 and 24hrs and repeated for ten replicates. The hexane extract at a concentration of 0.35 μL/cm2 gave a higher repellency of 76% as compared to other concentrations tested while the dichloromethane extract recorded 48% repellency at the same concentration after 24 hours. Thus, the hexane extract showed a significantly higher repellency effect on fruit flies as compared to dichloromethane at 0.35 μL/cm2. It could be concluded that hexane is a better candidate to be used in an integrated pest management program, and it could possibly reduce the problem of pesticide residues in the environment.